Long-Run Relationship Of Exports, Imports, Inflation And Exchange Rates In Indonesia - Gusti Firdaus; Yurina Yurina; Tarmizi Abbas (Journal of Malikussaleh Public Economics, 2021)
This study aims to the determine the short-run and long-run relationships of exports, imports, and inflation to the exchange rate. This study uses time-series data from 1988 to 2019. The Study employes Autoregressive Distributed Lag (ARDL). The results showed that in the short run, the exports positive and significantly influence the exchange rate. Imports negative and significantly influence the exchange rate, and inflation positive and significantly influences the exchange rate. Where as in the long run, exports positive and significantly influence the exchange rate. Imports negative and significantly influence the exchange rate, and the inflation positive but insignificantly influences the exchange rate.